Knowledge Power And Discipline : German Studies And National Identity - Bontempelli, Pier Carlo (Book collections on Project MUSE., 2004)
German Studies has confronted many crises, and yet it has managed to maintain its disciplinary system. Using the works of Michel Foucault and Pierre Bourdieu, Bontempelli investigates the principles of German Studies and critically reconstructs its history. Mindful of choice and domination operating at every turn, his book exposes the repressed social and political history of German Studies.